Application of LDR on Automatic Street Lights Using Electronic Workbench Simulation - Siti Nuraeni (International Journal of Research in Community Services, 2020)
LDR or Light Dependent Resistor is a resistor whose resistance value is influenced by the type of light received. In addition to having to be designed ON and OFF automatically and save electrical energy and human labor, the lighting of the street system is also monitored regularly, to ensure that there is no need for lights to be turned on, light sensors are needed. An example of its use is in garden lights and street lights that can turn on at night and turn off during the day automatically. Or we can also use it in our own room. This article will discuss the effect of the LDR light sensor on lamp control. Sensors are designed in conjunction with transistors. This transistor is used as a comparison of light entering the LDR sensor.